(untitled) (Journal of Surgical Sciences, 2020)
In sigmoid volvulus (SV), the sigmoid colon wraps around itself and its mesentery. Sigmoid volvulus accounts for 2% to 50% of all colonic obstructions and has an interesting geographic dispersion. SV generally affects adults, and it is more common in males. The etiology of sigmoid volvulus is multifactorial and controversial; the main symptoms are abdominal pain, distention, and constipation, while the main signs are abdominal distention and tenderness. Routine laboratory findings are not pathognomonic: Plain abdominal X-ray radiographs show a dilated sigmoid colon and multiple small or large intestinal air-fluid levels, and abdominal CT and MRI demonstrate a whirled sigmoid mesentery. Flexible endoscopy shows a spiral sphincter-like twist of the mucosa. The diagnosis of sigmoid volvulus is established by clinical, radiological, endoscopic, and sometimes operative findings. Although flexible endoscopic detorsion is advocated as the primary treatment choice, emergency surgery is required for patients who present with peritonitis, bowel gangrene, or perforation or for patients whose non-operative treatment is unsuccessful. Although emergency surgery includes various non-definative or definitive procedures, resection with primary anastomosis is the most commonly recommended procedure. After a successful nonoperative detorsion, elective sigmoid resection and anastomosis is recommended. The overall mortality is 10% to 50%, while the overall morbidity is 6% to 24%. Journal of Surgical Sciences (2019) Vol. 23(2): 90-94